FAKTOR-FAKTOR YANG MEMPENGARUHI INDEPENDENSI AUDITOR DALAM PENAMPILAN (Studi Empiris Pada Kantor Akuntan Publik Di Jawa Tengah) - Lutfina Amanda Putri, 13.05.52.0008; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of Audit Fee, Non Audit Service, Duration of Audit Relationship, Bonding Interests and Business Relationships with Clients, and the Size of Public Accounting Firms on Auditor Independence in Appearance. The population in this study were all auditors working at the Public Accountant Office in Central Java. Sampling in this study was conducted using convenience sampling techniques and the number of samples was 97 respondents. The primary data collection method used is the questionnaire method. Data were analyzed using multiple linear regression models. The results of this study indicate that the audit fee variable, non audit service, length of the audit relationship, the bonding of financial interests and business relationships with clients, and the size of the public accounting firm have a significant positive effect on auditor independence in appearance.